Performance of sideslip perching maneuver with an adaptive gain control feature - Feroskhan, Mir (2019)
The avian-inspired sideslip perching maneuver is an aggressive flight scenario that involves high turn rates and high rates of change of aerodynamic angles to decelerate and descend the aircraft rapidly for a precision landing. The occurrence of aerodynamic stall delay is unpredictable. Besides dynamic stall effects, state perturbations and model uncertainties heavily influence the accuracy of the landing and evidently, the success of the maneuver. This paper seeks to extend the convergence area related to the initial perching launch points and enhance the stability of the sideslip perching maneuver by formulating an adaptive gain sliding mode control technique. Based on a reference optimal sideslip trajectory generated by an optimization model, a comparative study between the proposed adaptive controller and a nominal sliding mode controller is carried out to evaluate their performances under different scenarios such as varying initial spatial and state conditions with induced state perturbations along the perching maneuver and dynamic stall uncertainties.